ANALISIS FAKTOR-FAKTOR KESULITAN BELAJAR PADA PEMBELAJARAN IPA KELAS VIII-A SMP NEGERI 1 ARAMO - Laia, Seniman (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
Based on the background of the problem, student activity seems to be lacking in the learning process, especially student activity in asking the teacher regarding the material discussed, students do not understand the material presented. This research aims 1) to determine the causes of students' learning difficulties at SMP Negeri 1 Aramo. 2) To determine the external factors of students' learning difficulties at SMP Negeri 1 Aramo. 3) to determine the internal factors of students' learning difficulties at SMP Negeri 1 Aramo. This type of research is qualitative with a case study approach. This research data was analyzed using data reduction, verification and drawing conclusions. The results of this research are that what causes students' learning difficulties is 1) students' lack of attention to the subject matter (concentration), concentration is meant to focus all attention on the learning situation and lack of concentration can cause learning difficulties. 2) lack of student participation and response when participating in teaching and learning activities (reaction). Reactions in learning activities require the involvement of physical and mental elements, as a form of reaction, so learning must be active. 3) students are slow in understanding the material (comprehension) and this results in low student learning outcomes. Suggestions: As the key to successful learning and not experiencing learning difficulties, students must increase motivation, concentration, reactions, understanding of the material and maximum learning results. Students also have to choose what activities are more useful to do at home. It is hoped that teachers will further optimize the potential of students who experience learning difficulties or not by increasing media or learning that involves interesting activities.